2008
DOI: 10.1136/thx.2007.086785
|View full text |Cite
|
Sign up to set email alerts
|

Markers of treatment failure in hospitalised community acquired pneumonia

Abstract: Background: Lack of response to treatment in community acquired pneumonia (CAP) worsens outcome. We evaluated the systemic cytokine profile (tumour necrosis factor a, interleukin (IL)1, IL6, IL8 and IL10), C reactive protein (CRP) and procalcitonin (PCT) in patients with CAP who had treatment failure. Methods: A prospective study was performed in hospitalised patients with CAP. Cytokines, PCT and CRP measurements were obtained on day 1 and after 72 h of treatment. Treatment failure was the endpoint evaluated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
109
2
10

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 35 publications
16
109
2
10
Order By: Relevance
“…16 Additionally, others have defined NRP in hospitalized CAP patients as those with lack of response after 3 to 4 days of appropriate antibiotic treatment, often with clinical deterioration. 7,8,9,17 The second portion of our definition of NRP, 10 days of antibiotic therapy without improvement, is consistent with the observation that 90% of pneumonia-related hospitalizations in a cohort of 944 CAP patients who were treated as outpatients occurred within 10 days of treatment. 22 These same authors concluded that "the incidence of hospitalization within 10 days of beginning outpatient treatment for CAP is a reasonable screening tool for unsatisfactory quality of care in this illness."…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…16 Additionally, others have defined NRP in hospitalized CAP patients as those with lack of response after 3 to 4 days of appropriate antibiotic treatment, often with clinical deterioration. 7,8,9,17 The second portion of our definition of NRP, 10 days of antibiotic therapy without improvement, is consistent with the observation that 90% of pneumonia-related hospitalizations in a cohort of 944 CAP patients who were treated as outpatients occurred within 10 days of treatment. 22 These same authors concluded that "the incidence of hospitalization within 10 days of beginning outpatient treatment for CAP is a reasonable screening tool for unsatisfactory quality of care in this illness."…”
Section: Discussionsupporting
confidence: 53%
“…15 This same group prospectively studied 453 patients with CAP admitted to two Spanish hospitals and observed treatment failure in 18%. 17 Roson et al performed an observational study of 1,383 CAP patients hospitalized in Barcelona. 9 Early failure, defined as lack of response or worsening of clinical or radiologic status at 48-72 hours requiring changes in antibiotic therapy or invasive procedures, was experienced by 6% of these patients, predominantly due to progressive pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Andererseits hatten niedrige CRP-bzw. PCT-Werte am Tag 1 einen hohen negativen pr ä diktiven Wert f ü r fr ü hes Therapieversagen [119] .…”
Section: Therapiesteuerungunclassified